Determinant of Accounting Understanding - Merry Susanti, Sufiyati, Sofia Prima Dewi, (Jurnal Ekonomi, 2020)
: Â This study was made to determine the effect of perception of intellectual intelligence, emotional intelligence, spiritual intelligence, and learning behavior on understanding accounting. The collection method was carried out by distributing questionnaires to Tarumanagara University students. The questionnaire was distributed from March to May 2019. Data processing methods were carried out using partial least square-structural equation modeling (PLS-SEM). The results showed that emotional intelligence and learning behavior have no influence students on understanding accounting. Perception of intellectual intelligence possessed by students only influence on understanding Accounting Principle 1 and Accounting Principle 2. Emotional intelligence has no influence on understanding accounting. Spiritual intelligence possessed by students only influences on understanding of Accounting Principle 1. Learning behavior has no influence on understanding accounting.